The Residents of An Economy : The Residents of An Economy. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
Based on jurisdictional grounds, this paper suggests that for statistical, analytical, and policy purposes, the residents of a given economy can best be defined in terms of their presence in the territory of that economy. The paper recommends that this concept, which is underlying the definitions of general government, individuals, and enterprises in the 1968 version of the United Nations' A System of National Accounts and the 1977 version of the International Monetary Fund's Balance of Payments Manual, should continue to be used for measuring gross domestic and gross national product as well as international transactions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: General Aggregative Models; International Agreements and Observance; International Organizations